Comparison of Forensic Virtual Autopsy and Conventional Autopsy Findings in China: A 10-year Retrospective Study - Ya-Wen Liu; Zhuo-Qun Wang; Zhi-Ling Tian; He-Wen Dong; Yuan-Yuan Liu; En-Hao Fu; Jiang Huang; Dong-Hua Zou; Ning-Guo Liu (Journal of Forensic Science and Medicine)
Background: This study evaluates the noninvasive virtual autopsy (virtopsy), which uses imaging technologies like computed tomography (CT) and magnetic resonance imaging to examine deceased internal structures, as an alternative to traditional autopsies due to its less invasive nature and greater family acceptance. Aims and Objectives: The aim was to assess virtopsy’s effectiveness by comparing it with traditional autopsies in 322 cases from the Academy of Forensic Science in China over a decade, focusing on various anatomical regions and tissues. Materials and Methods: Postmortem computed tomography (PMCT) and PMCT angiography (PMCTA) were performed on 204 cadavers before traditional autopsies, with the agreement between virtopsy and autopsy findings assessed using Cohen kappa values. Results: Virtopsy showed higher sensitivity in detecting fractures, particularly in hard-to-access bones, but was less sensitive to rib fractures. Autopsy was more effective for intracranial injuries and organ pathologies, while PMCTA excelled at revealing vascular lesions and injuries. Conclusion: Virtopsy is effective for certain tissues and organs, serving as an auxiliary and guiding tool in traditional autopsies, thus enhancing forensic diagnosis and case resolution.